PENGARUH LIKUIDITAS, LEV ERAGE, SALES GROWTH, OPERATING CAPACITY, DAN UKURAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS: (Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di BEI Tahun 2017-2018) - Oktaviani, Bella (J-MABISYA, 2020)
This research aims to analyze the effect of liquidity, leverage, sales growth, operating capacity, and size firm towards financial distress. The objects of this research are manufacturing companies customer good industry sector listed in Bursa Efek Indonesia for period 2017-2018. Selection of the sample is determined based on purpose sampling method. Based on predetermined criteria, there are 30 companies. Sources of data in this research is secondary data which is derived from BEI’s official site (www.idx.co.id). Analysis method of the data using panel data regression. The result of this research are leverage variable has negative effect towards financial distress. Meanwhile operating capacity variable and size firm have positive effect towards financial distress.Variable liquidity and sales growth haven’t effect towards financial distress.